Design and fabrication of a stretchable triboelectric nanogenerator - Zhang, Ruo Qing (Nanyang Technological University, 2021)
Rapid advancements in flexible and wearable electronics have driven the demand for power sources that are soft and deformable. Recently, triboelectric nanogenerators (TENGs) have shown great potential as sustainable power sources for harvesting mechanical energy from human motion. However, the rigidity of traditional metal-based electrodes poses a challenge in the fabrication of stretchable TENGs. Moreover, the sharp rise in the resistance of these electrodes at high strains further limits the stretchability of the device. Conductive polymers are promising materials that can replace traditional metal electrodes. In particular, polypyrrole (PPy) is attractive because of its relatively high conductivity and environmental stability. In this work, Poly(vinyl alcohol)-Glycerol-Polypyrrole (PVA-Gly-PPy) solid and liquid electrodes were prepared through in situ chemical polymerization of pyrrole in the presence of PVA and glycerol. The use of PPy endowed the electrodes with high conductivity. The conductivity of PPy is known to arise from its π-conjugated backbone and through doping. Here, FeCl3 was used as the oxidant. PVA was used as the matrix material to blend with PPy and to impart mechanical strength. Additionally, the polymer matrix provides the network for electron and ion transport. Glycerol was used as the plasticizer to improve stretchability and stability of the electrodes. The thermal, mechanical and electrical properties of the electrodes were studied and analyzed. Finally, the solid electrode-based TENG (SE-TENG) and liquid electrode-based TENG (LE-TENG) in the single electrode mode were fabricated and the output performance of the TENGs were evaluated and compared. Both the TENGs could successfully harvest mechanical energy from human motion, even under strain.